Lithological attributes of hd-001 well, shallow offshore, Niger delta basin, Nigeria - A. Olatunji, Olubusayo; A. Okosun, Edward; S. Onoduku, Usman; B. Alkali, Yahya (International Journal of Advanced Geosciences, 2020)
Lithological analysis was carried out on 96 ditch cuttings samples from HD-001 well located within the shallow offshore Niger delta basin, Nigeria. Three lithofacies sequences were delineated by the integration of wireline logs textural/lithologic attritudes and the distribution of index accessory minerals. They are transitional paralic, paralic and marine paralic sequences. The lithologic, textural and wireline log data indicate that the entire interval studied in the HD-001 well belongs to the Agbada Formation. The Formation is made up of alternating sand and shale units which suggests rapid shoreline progradation. The grain size increases from essentially fine to medium-grained at the basal part of the well to dominantly coarser grain at the upper part. The index accessories recognize shallow marine to coastal deltaic settings environment of deposition. Sand bodies which represent sub-environments within those settings are deposited in sequences. Each sequence begins with a transgressive phase followed by significant regressions.Â Â Â